Phytochemical screening and in silico pharmacological profiling of ethanolic extract of Aframomum melegueta for prostate carcinoma - Asiat NaAllah, Yusuf Oloruntoyin Ayipo&, Damilola Ibukun Komolafe, Sobiat Solihu, Bukola Bamidele, Mutiu Adewunmi Alabi, Abdul-Azeez Balogun, Azeemat Titilola Abdulazeez, Mohd Nizam Mordi (Journal of Applied Pharmaceutical Science, 2021)
Prostate remains the most common cancer in men and among the leading causes of cancer-related deaths worldwide. However, incessant resistance by the disease, inadequate effective prevention and treatment strategies, and affordability are major challenges in curtailing its threat. This study is aimed at the identification of potential antiprostate phytochemicals in ethanolic extract of Aframomum melegueta, acting through a “one-drug-multipletarget” approach using a network of computational tools. Using glide docking simulations, the inhibitory potentials of the phytoconstituents were evaluated against three receptors relevant to prostate therapy: the human androgen receptor from protein data bank (PDB 5T8E), cyclooxygenase-2 (PDB 4PH9), and cytochrome P450 17A1 (PDB 3RUK). The bioactivity, physicochemical, and toxicological profiles, and mutagenicity of the selected phytochemicals were predicted in silico using Prediction of Activity Spectra for Substances online, SwissADME, and VEGA ToxRead tools. From molecular docking, the phytochemicals, caryophyllene, humulene, 5α-androstan-16-one, [1,3] benzodioxolo[5,6-c]phenanthridine, and d-norandrostane (5α;14α) possess a good binding affinity for each receptor in similarity with the co-crystallized ligands and mostly in higher terms than the reference drugs. They are strongly predicted as antineoplastic, apoptosis agonists, CYP2J substrates, NADP+ inhibitors, and agents for prostate disorder. They demonstrate interesting drug-like profiles with a low expression for toxicity and mutagenicity. The easily accessible phytochemicals are promising potentials, amenable for translational designs into effective antiprostate therapeutics upon further study.
Keywords: Aframomum melegueta, prostate cancer, molecular docking, mutagenicity, ADMET, drug discovery.